2020
DOI: 10.3389/fmicb.2020.01799
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence-Associated Markers in Campylobacter Strains From Diarrheic and Non-diarrheic Humans in Poland

Abstract: Campylobacteriosis is one of the most common causes of bacterial gastroenteritis. However, the clinical course of the illness varies in symptoms and severity. The aim of this study was to characterize Campylobacter jejuni (34 isolates) and C. coli (9 isolates) from persons with diarrheal and non-diarrheal stools at the time of examination and fecal sampling, in Poland by using whole-genome sequencing (WGS). Multilocus sequence typing (MLST) analysis revealed a high diversity with a total of 20 sequence types (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 71 publications
5
36
3
Order By: Relevance
“…Notably, ST814-661 strains did not carry the complete cmeB gene that encodes a multidrug efflux pump, which may have contributed to reduced TET and fluoroquinolone resistance, despite the presence of tetO and gyrA T86I (Pumbwe and Piddock, 2002). Comparable levels of gyrA T86I carriage and CIP resistance concordance have also been previously reported (Wysok et al, 2020). While significant differences in the prevalence of genes associated with specific biological functions were identified between MLST types (Appendix S2), no COG categories were over-represented in ST48-48 as compared to ST257-257.…”
Section: Discussionsupporting
confidence: 52%
“…Notably, ST814-661 strains did not carry the complete cmeB gene that encodes a multidrug efflux pump, which may have contributed to reduced TET and fluoroquinolone resistance, despite the presence of tetO and gyrA T86I (Pumbwe and Piddock, 2002). Comparable levels of gyrA T86I carriage and CIP resistance concordance have also been previously reported (Wysok et al, 2020). While significant differences in the prevalence of genes associated with specific biological functions were identified between MLST types (Appendix S2), no COG categories were over-represented in ST48-48 as compared to ST257-257.…”
Section: Discussionsupporting
confidence: 52%
“…Apart from multilocus sequence typing (MLST) schemes, based on the analysis of the sequence of several house-keeping genes, WGS also allows to predict relevant phenotypes, such as antibiotic resistance, in Campylobacter (Zhao et al, 2016). Moreover, recent studies have found high concordance between the presence of antimicrobial resistance determinants in WGS data and phenotypic resistance among Campylobacter isolates from Latvia (Meistere et al, 2019), England and Wales (Painset et al, 2020), and Poland (Wysok et al, 2020), supporting the use of WGS data as a good predictor for phenotypical antimicrobial resistance.…”
Section: Thermophilicmentioning
confidence: 99%
“…In this study the presence of aadE gene was detected in 13,9% of the C. jejuni isolates. The literature review on this gene usually shows a low prevalence and in several published papers we noted low prevalence (Cantero et al, 2018;Obeng et al, 2012;Wysok et al, 2020;Du et al, 2018) with 6.3%, 0%, 0%, 0.8%, respectively.…”
Section: Presence Of Resistance Genes In C Jejunimentioning
confidence: 54%